The taxonomy and nomenclature of Kalanchoe elizae (Crassulaceae subfam. Cotyledonoideae) from south-tropical Africa, and its heterotypic synonyms - Smith, Gideon F. (Phytotaxa, 2025)
The name Kalanchoe elizae (Crassulaceae subfam. Cotyledonoideae) is in use for an accepted species from Malawi and Mozambique in south-tropical Africa. The taxonomy and nomenclature associated with the name are discussed and clarified. No material was cited in the protologue of the name K. elizae, and to date it has not been typified, which is done here. The typification of the name K. laurensii, a heterotypic synonym of K. elizae, is also discussed. It is also shown that the combination Cotyledon elizae was validly published by Alwin Berger, who, earlier, also validly published the name K. elizae.